Is children's weight a public health or a private family issue? A qualitative analysis of online discussion about National Child Measurement Programme feedback in England - B. E. Kovacs; F. B. Gillison; J. C. Barnett (BMC, 2018)
Abstract Background The National Child Measurement Programme (NCMP) is a child weight monitoring system in England, taking place in the first and final years of primary school. Many local authorities consider it important to inform parents if their child is overweight, and do so by letter alongside the offer of support and advice. Such letters have been met with mixed reactions from parents, but research seeking to better understand parents' responses is often limited by reliance on survey data and low participation rates. This study aimed to collect a broad variety of perspectives on the programme by analyzing views expressed in parent-to-parent discussions posted online. Methods UK-based online parenting fora were used to identify discussion threads based around the NCMP between 2010 and 2017. Thirty-one discussion threads from two parent fora were identified. Thematic analysis was used to identify themes in these data. Results The primary themes identified related to (1) the legitimacy of feedback and judgement from health professionals, (2) the relative importance of collecting population level data above individual preferences, and (3) risks versus benefits of having conversations with children about weight. Most threads adopted an 'argument, counter-argument' format, providing two sides to each issue raised. Information and opinions consistent with public health messages were frequently provided, such as how data are used, that feedback is intended to be helpful, and the importance of collecting national data. There was little evidence of individual parents shifting their views in response to others' arguments. Conclusions This study provides novel insight into peer-to-peer debates about the NCMP, including the arguments parents find convincing and acceptable for and against a national programme to weigh children and provide feedback to parents about their weight. Online fora were used as an opportunity to express criticism or distress, but also to seek advice from peers regarding concerns about whether or not to opt-out. Thus, both general issues related to the legitimacy of population screening and outcomes for individual children were of concern to parents.